White matter damage in Alzheimer's disease assessed in vivo using diffusion tensor magnetic resonance imaging - Bozzali, M; Falini, A; Franceschi, M; Cercignani, M; Zuffi, M; Scotti, G; Comi, G; Filippi, M (Journal of neurology, neurosurgery and psychiatry, 2002)
Objective: To investigate the extent and the nature of white matter tissue damage of patients with Alzheimer's disease using diffusion tensor magnetic resonance imaging (DT-MRI). Background: Although Alzheimer's disease pathology mainly affects cortical grey matter, previous pathological and MRI studies showed that also the brain white matter of patients is damaged. However, the nature of Alzheimer's disease associated white matter damage is still unclear. Methods: Conventional and DT-MRI scans were obtained from16 patients with Alzheimer's disease and 10 sex and age matched healthy volunteers. The mean diffusivity (D̅), fractional anisotropy (FA), and inter-voxel coherence (C) of several white matter regions were measured. Results: D̅ was higher and FA lower in the corpus callosum, as well as in the white matter of the frontal, temporal, and parietal lobes from patients with Alzheimer's disease than in the corresponding regions from healthy controls. D̅ and FA of the white matter of the occipital lobe and internal capsule were not different between patients and controls. C values were also not different between patients and controls for any of the regions studied. Strong correlations were found between the mini mental state examination score and the average overall white matter D̅ (r=0.92, p<0.001) and FA (r=0.78; p<0.001). Conclusions: White matter changes in patients with Alzheimer's disease are likely to be secondary to wallerian degeneration of fibre tracts due to neuronal loss in cortical associative areas.